Exploring Psychological Barriers in Educating the Transgenders: A Case Study - Shahana Dawaid; Dr. Mohammad Sohail; Dr. Muhammad Idrees, (Dialogue Social Science Review (DSSR), 2025)
The psychological barriers that transgender students face in educational environments are examined in this qualitative case study. This study identifies and investigates the complex relationships between many issues that limit transgender people's educational goals using semi-structured interviews with ten transgender students. According to the research, internalized transphobia, fear, sorrow, and rejection anxiety are among the major psychological barriers that transgender students must overcome. Inadequate support networks, discriminatory practices, and inequality in educational institutions all contribute to these barriers. This study emphasizes how important it is for educators, legislators, and mental health specialists to address these psychological obstacles and establish welcoming, encouraging environments that promote transgender children' academic achievement and general well-being. According to Kirk and Kulkarni (2006), the term "transgender" refers to a person whose gender identification or expression differs from the one they were assigned at birth. Transgender youth frequently have low levels of school attendance and academic achievement, as well as high rates of despair and self-harm (Kosciw, 2009). According to Ryan, Russell, Huebner, Diaz, and Sanchez (2010), transgender kids' and their families' experiences are hardly mentioned in educational literature. Few studies concentrate exclusively on transgender adolescents in education since transgender issues are frequently combined alongside lesbian, gay, and bisexual communities (Irwin, 2002). This study's objectives were to: explore the psychological barriers in educating the transgender, The unique experiences of a transgender child who has encountered numerous challenges were revealed in this study. An close look into the participants' transgender difficulties during their education was obtained through the use of a qualitative case study and open-ended questions.